Determination of the Total Mass of Antioxidant Substances and Antioxidant Capacity per Unit Mass in Serum Using Redox Titration - Meijuan Zhang; Na Liu; Hui Liu (Bioinorganic Chemistry and Applications)
Objective. Total antioxidant capacity in serum is determined by the total mass of antioxidant substances and the antioxidant capacity per unit mass (average activity). The purpose of this study was to develop a method to determine the mass of antioxidant substances and average activity in human serum. Methods. Specimens of serum were collected from 100 subjects each from two different age groups: over 75 years old and 20–40 years old. The test serum was diluted into a series of concentrations, following which standard oxidation agents (KMnO4 for potassium permanganate method and I2 for iodimetry) were added to each concentration of serum, and the absorbance of the mixture (optical density, OD) was measured. The OD value and logarithm of dilution factor (lgT) at the end of the titration were obtained, from which the lgT could be considered as mass of antioxidant substances (M). Total antioxidant capacity (Ta) was calculated with the equation Ta = 100/(OD1 + 2 * OD2 + 2 * OD3 + 2 * OD4 + OD5), and average activity (A) was calculated as A = Ta/M. Results. The potassium permanganate method generated similar results to the iodimetric method. Compared with the younger group, total antioxidant capacity in the over-75-year age group was found to be significantly reduced, along with a decrease in the mass of antioxidant substances and average activity levels in human serum. Conclusions. The approach described in this paper is suitable for determining the average activity and mass of antioxidant substances in human serum.